Progress Report in Neuroscience and Education: Experiment of Four Neuropedagogical Methods - Leila Elouafi; Said Lotfi; Mohammed Talbi (MDPI AG, 2021)
We endeavor through this work to demonstrate the effects of the introduction of neuroeducation data in schools and their application, via an experiment of neuropedagogical methods, to respond to the hypothesis that the contribution of neuroeducation may be beneficial for learning. During this study we designed four neuropedagogical methods and to measure their effect on the learning of students in the classroom we used an evaluation grid comprising six psychopedagogical parameters. The results show that no statistically significant variation of these psychoeducational parameters is observed between sexes. However, a variation is recorded for the four neuropedagogical methods between the groups in pre-test and post at the levels of the mean scores ranging from 5.15% to 440%.